Perceptions of dentists, dentistry undergraduate students, and the lay public about dental sedation Percepção de cirurgiões-dentistas, acadêmicos de odontologia e público leigo sobre sedação em odontologia - Luciane Ribeiro de Rezende Sucasas da Costa; Andréia Diniz Dias; Luciana Silva Pinheiro; Maria Edwiges Pinheiro de Souza Chaves; Raíssa de Aquino Rodrigues Ferreira; Roberta Barros de Almeida; Alessandra Rodrigues de Almeida Lima (University of São Paulo, 2004)
Sedation is an option for controlling fear and anxiety related to a visit to the dentist. The goal of this study was to capture, by means of a questionnaire, the perceptions of twenty dentists, twenty dental students and twenty lay people concerning the use of sedatives in a dental environment. The responses were evaluated using the quantitative-interpretative method. Dentists: 75% had knowledge of sedatives in a dental setting, but their actual use was mentioned by only three. As far as the use of sedatives by dentists is concerned, one considered it "risky" and 19 were favorable. Two affirmed that sedation does not present risks. Eighteen said they would be able to react to a medical emergency. Dental students: 60% said they were aware of the topic, in theory. Nineteen expressed interest in the topic. Fifteen claimed there were risks associated with the technique. Twelve (60%) have the theoretical knowledge to deal with a medical emergency in the dental office. Lay public: Seven (35%) responded that they felt some discomfort during dental treatment, because of fear (n=6) and equipment noise (n=2). Five said they would go to the dentist more often if there was a way to reduce the discomfort. Half of those interviewed indicated that they knew what sedation was. Sixteen favored using it for dental treatment. Seven thought that there were no risks when sedation is carried out. It was concluded that few participants in any of the three categories felt confident about the topic, though they demonstrated interest. The population in general felt optimistic, while practicing dentists and dental students complained of a lack of exposure to the subject at dental school. A sedação constitui-se em opção no controle do medo e da ansiedade relacionados à visita ao dentista. Propôs-se captar a percepção de 20 cirurgiões-dentistas, 20 acadêmicos de odontologia e 20 leigos sobre a utilização de recursos sedativos em ambiente odontológico, através da aplicação de formulários. As respostas foram avaliadas através de método quantitativo-interpretativo. Cirurgiões-dentistas: 75% tinham conhecimento do uso de sedativos em consultório odontológico, sendo que sua prática efetiva foi mencionada por apenas três. Quanto ao uso de sedativos por dentistas, um considerou "arriscado" e 19 manifestaram-se favoráveis. Dois afirmaram que a sedação não oferece riscos. Dezoito disseram saber reagir frente a emergência médica. Acadêmicos de odontologia: 60% admitiam conhecer o tema, em teoria. Dezenove expressaram interesse no assunto. Quinze afirmaram haver riscos associados à técnica. Doze (60%) tinham o conhecimento teórico para conduta frente a uma emergência médica no consultório. Público leigo: Sete (35%) responderam que sentiam algum desconforto no tratamento odontológico, representado pelo medo (n=6) e o ruído dos equipamentos (n=2). Cinco disseram que iriam mais freqüentemente ao consultório odontológico se houvesse algum meio para reduzir o desconforto. Metade dos entrevistados relatou saber o que é sedação. Dezesseis foram favoráveis à sua realização para tratamento odontológico. Sete julgaram que não há riscos quando se faz sedação. Concluiu-se que poucos participantes, dentro das três categorias, estiveram seguros com relação ao assunto, embora tenham demonstrado interesse. A população em geral sentiu-se otimista, enquanto que CDs e acadêmicos queixaram-se da pouca vivência do tema nas faculdades.